Preoperative psychological factors predict talonavicular fusion outcomes in Muller-Weiss disease - Liu, Xiaocong; Pan, Yalei; Cao, Shihang; Lu, Jun; Xu, Junkui (Frontiers in Psychiatry, 2025)
ObjectiveThe aim of this study was to investigate the association between preoperative anxiety and depression and surgical outcome in patients with Müller-Weiss disease (MWD).MethodsThis retrospective study included 41 patients diagnosed with MWD who underwent talonavicular joint fusion at the Foot and Ankle Surgery Department of Xi'an Honghui Hospital between April 2014 and September 2024. Patients were stratified into two groups based on preoperative anxiety and depression symptoms: Group A (symptomatic) and Group B (asymptomatic). Preoperative and final follow-up assessments included the Hospital Anxiety and Depression Scale (HADS), Visual Analogue Scale (VAS) for pain (0–100 mm), and American Orthopedic Foot and Ankle Society (AOFAS) score.ResultsAmong 41 patients with complete follow-up, 20 (49%) exhibited preoperative anxiety and depression symptoms. Both groups demonstrated significant improvement in clinical outcomes following talonavicular joint fusion; however, Group A showed inferior overall outcomes compared to Group B. There is a significant negative correlation between AOFAS score improvement and preoperative anxiety levels (r = -0.62, P < 0.05).ConclusionIn patients undergoing talonavicular fusion surgery the presence of high levels of depression and anxiety is associated with inferior post-operative outcomes; moreover the level of anxiety correlates with post-operative improvement in function, emphasizing the importance of addressing psychological factors in treatment planning.